Analysis of Online Newspapers’ Framing Patterns of COVID-19 in Nigeria - Onwe, Emmanuel Chike; Chukwu, Joseph; Nwamini, Samuel Chukwuemeka; Nwankwo, Simon Ugochukwu; Elem, Stephen; Ogbaeja, Nelson Iroabuchi; Nwasum, Chinedu Jude; Nwakpu, Ekwutosi Sanita; Ogbodo, Jude Nwakpoke (European Scientific Journal, ESJ, 2020)
Online newspapers have become one of the leading hubs for information disemination especially with the advent of web 2.0. Internet penetration in Nigeria has also contributed immensily in making diferent news contents avaliable on the web. Many people now depend on their smart phones, laptops and tablets to access news from the internet. Articles in online newspapers on COVID-19 are shared social media platforms such as Facebook, Twitter, WhatsApp, Instagram, Telegram amongst others, making it possible for stories to easily go viral. The manner in which online newspapers frame issues of public importance determines the level of knowledge of online news consumers and their perception of the issues. This study investigates how three online newspapers framed the outbreak of COVID-19 pandemic in Nigeria. Anchored on Frame Analysis Theory, the study also employs Relational Content Analysis as its design. Finding shows that fear and death, government and/political influence, and palliative frames emerged as the dominant frames across the three online newspapers – Sahara Reporters, Premium Times and Daily Post studied for three months.The implication of this finding is that online newspapers reported COVID-19 outbreak in ways that made the audience jittery before the eventual outbreak of the pandemic. The study recommends that online newspapers should harp more on palliative as against fear and death frames in reporting any health emergancy in the future.